Co-design of mechanical and electrical parameters in wind turbine gearbox-generator systems - Chen, Ruibo; Wu, Zhonghua; Sun, Jinwei; Qin, Datong; Zhao, Chuanwei (Sound & Vibration, 2026)
Conventional design practices for wind turbine drivetrains commonly adopt a segregated workflow where the gearbox and electrical machine are developed independently. Such a decoupled strategy overlooks inherent electromechanical coupling constraints, thereby imposing fundamental limits on attainable power density and dynamic behavior of the entire transmission assembly. To mitigate these limitations, this work presents a hierarchical integrated parameter co-design framework for wind turbine gearbox–generator systems, which implements progressive optimization from system-level to component-level, while synchronously satisfying static performance and dynamic response requirements. In the first design stage, an integrated initial parameterization scheme is formulated via finite element analysis (FEA) and numerical computation, with objectives to elevate system power density and suppress amplitudes of internal dynamic excitations. The optimized parameters from this stage serve as baseline inputs for the second stage. An electromechanically coupled dynamic model is then established to quantify correlations between key mechanical structural parameters (gearbox bearings, hollow shafts, splines, ring gear bolt stiffness) and generator electromagnetic/structural parameters, as well as overall system dynamic characteristics. Sensitive design variables are identified via correlation analysis, and a Kriging surrogate model is constructed to approximate nonlinear input–output relationships efficiently. Multi-objective component optimization is subsequently performed using the surrogate model. Finally, vibration attenuation and load reduction performances of the baseline and optimized drivetrain configurations are systematically compared under rated and variable operating conditions.